Comprehensive review of caries assessment systems developed over the last decade - Abhishek Mehta (Revista Sul-Brasileira de Odontologia, 2013)
World Health Organization (WHO) in the year 2007 recognized the growing burden of oral diseases worldwide and emphasized the need to scale up action based on comprehensive data collection systems. In view of the global epidemic of untreated caries in children there is an urgent need to establish a scoring system that both assesses and quantifies various advanced stages of caries. Furthermore, the available data are not readily comparable due to the different scoring systems used. The DMF index despite having limitations has been widely utilized in oral epidemiological surveys. It is recommended by the WHO for measuring and comparing the experience of dental caries in populations. The path of future research in caries epidemiology will depend on finding an ideal caries index. Objective: This review is prepared to present and critically evaluate various new caries assessment systems that have been developed in the last decade. Literature review: A literature search was done to find out major caries assessment systems developed over last decade, it revealed there were five new indices developed to assess caries. These indices were critically evaluated to list their strengths and limitations. Conclusion: There are many promising new caries indices purposed, but still there is a need for further studies to evaluate their validity and reliability before they can replace DMFT index.